PRODUK KREATIF DAN KEWIRAUSAHAAN DALAM PEMBUATAN KUE PAO - Damanik, Dennys Paulus Parlindungan; Simanjuntak, Demak Claudia Yosephine; Sari, Ike Rukmana; Purnasari, Nina; William, William (Jurnal Pengabdian Bukit Pengharapan, 2025)
Creativity is the process of turning new and innovative ideas into tangible results, practices and solutions. This is an important component of entrepreneurship, because individuals must be creative to identify and exploit opportunities. Where existing opportunities can be a solution for the community to meet their daily needs, especially for teenagers who have an interest and intention in building their business. Where high school level teenagers usually lack motivation to develop themselves. This community service activity is aimed at teenagers at high school level with the aim of motivating them to develop their creativity so that it is hoped that young entrepreneurs will emerge who will strengthen MSMEs in Indonesia. The methods used in this community service include presentations and questions and answers so that participants can better understand the topic and be motivated to develop their creativity. The results of this activity were quite satisfactory, with several participants starting to open small businesses such as selling snacks made by themselves in the school environment and in their home environment